Isotope analyses of amino acids in fungi and fungal feeding Diptera larvae allow differentiating ectomycorrhizal and saprotrophic fungi‐based food chains. (31st August 2020) - Pollierer, Melanie M.; Scheu, Stefan; Tiunov, Alexei V.
Abstract: Both ectomycorrhizal (ECM) and saprotrophic fungi are fundamental to carbon and nutrient dynamics in forest ecosystems; however, the relative importance of these different fungal functional groups for higher trophic levels of the soil food web is virtually unknown. To explore differences between fungal functional groups and their importance for higher trophic levels, we analysed isotopic composition of nitrogen and carbon in amino acids (AAs) and bulk tissue of leaf litter, fungi and fungal‐feeding Diptera larvae. By accounting for isotopic variability of utilized substrates, compound‐specific isotope analyses of nitrogen in AAs yielded more realistic results for the trophic position of fungi than bulk isotope analyses, with converging trophic positions of saprotrophic and ECM fungi. Saprotrophic and ECM fungi possessed different AA δ 13 C signatures separating fungal functional groups and their consumers in fingerprinting approaches, thereby allowing to trace energy fluxes from these basal resources to higher trophic levels. A pronounced isotopic fractionation even in essential/source AAs of fungal‐feeding Diptera larvae necessitates further studies on tissue‐/compound‐specific isotopic differences in fungi and on potential supplementation by gut micro‐organisms. The results highlight the potential of compound‐specific isotope analysis of amino acids to identify and integrate contributions of different fungal functional groups to higher trophic levels in soil food webs. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.